Visible history of Tuva in photo documents at the National Archives of the Republic of Tuva - Bazyr, Ruslana N. (The New Research of Tuva, 2020)
The article analyzes the photographic collections at the National Archives of the Republic of Tuva (prior to 07.04.2020 known as the State Archives of RT. We have provided a classification and in-depth description of the main collections, which include photographs. The archives store 4,466 master negatives, 5,115 positive prints, of which 1,832 in thematic albums. Finally, 95 archival units (files) are recorded onto CD-ROMs. The archives have been providing an option to submit photographs since 1989, with the bulk of them coming from regional organizations and private individuals. The archives also practice proactive collecting of photodocuments. Our classification runs along the lines of functional purpose, of the image colo, and of the material of the carrier, among other factors. Documents can thus be classified into photographs of events (about 35%); portrait photography (about 39%);and landscape photos or those featuring certain items on the ground (about 25%). The most popular among the photodocuments are those which belong the period of the Uriankhai Territory (1914-1921) and the Tuvan People’s Republic (1921-1944). They are scattered among several collections. Even better known are the photodocuments belonging to the fond titled "A collection of photographs related to the history of Tuva" (1913-1940) taken by ethnographer V. P. Ermolaev. Beside these, the collections hold many photographs of both public figures, ordinary workers and people who have made a significant contribution to the development of the region. All of these are important sources for studying the history of Tuva. The text of the article is illustrated with several photographs from the collections of the Archives.